Implementation of the Grammatical Translation Method in I'rob Jurumiyah Learning at Madrasah Diniyah An-Nur Batu - Nabiilah, Alaikin; Hasanah, Mamluatul; Faisol, Faisol (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2024)
Madrasah Diniyah An Nuur Batu faces challenges in teaching Arabic grammar (nahwu i'rob jurumiyah) due to traditional methods. This research investigates the effectiveness of the grammatical translation method in addressing these challenges. The study employed a qualitative case study approach, gathering data through interviews with educators, the headmaster, and students, as well as observations and document analysis. The findings reveal that the grammatical translation method significantly enhances i'rob jurumiyah learning at the madrasah. The method involves using the students' native language as the medium of instruction, with the teacher actively presenting material and students passively receiving it. This approach focuses on teaching grammatical rules, leading to improved understanding and application of nahwu concepts. The supporting factors for the implementation of the grammatical translation method in learning i'rob jurumiyah at Madrasah Diniyah An Nuur Batu are adequate facilities, a supportive Arabic language learning environment and the background of students, the creativity of educators in teaching, the existence of nadzom by Madrasah Diniyah An Nuur Batu, and the existence of additional exciting methods